Myelofibrosis and allogeneic transplantation: critical points and challenges - Ranalli, Paola; Natale, Annalisa; Guardalupi, Francesco; Santarone, Stella; Cantò, Chiara; La Barba, Gaetano; Di Ianni, Mauro (Frontiers in Oncology, 2024)
New available drugs allow a better control of systemic symptoms associated with Myelofibrosis (MF) and splenomegaly but they do not modify the natural history of progressive and poor prognosis disease. Thus Haematopoietic Stem Cell Transplantation (HSCT) is still considered the only available curative treatment for patients with MF.Despite the increasing number of procedures worldwide in the last years HSCT for MF patients remains challenging. An increasingly complex network of the patient, disease, and transplant-related factors needs to be considered to understand the need and opportunity of the procedure. Unfortunately, prospective trials are often lacking in this setting, making an evidence-based decision process particularly arduous. In the present review, we will analyze the main controversial points of allogeneic transplantation in MF i.e the development of more sophisticated models for the identification of eligible patients; the need for tools offering a more precise definition of expected outcomes combining comorbidity assessment and factors related to the procedure; the decision-making process about the best transplantation time; the evaluation of the most appropriate platform for curative treatment; the impact of splenomegaly and splenectomy on outcomes.